The Phenomenon of the Urban Mummy. Issue 6 (6th August 2015) - Harding, Brett E.; Wolf, Barbara C.
Abstract: The environmental mummification of a body in an urban setting is an unusual event. Florida is known for its high temperatures and humidity, which typically result in the rapid putrefaction of bodies. However, under certain circumstances, Florida's climate provides an environment suitable for mummification, typically in isolated areas. We previously reported a case of a homicide/suicide in a residential neighborhood in which the mummified remains were undetected for several years. We have subsequently encountered two additional cases in which mummified bodies were discovered in urban settings. Presented in the historical context of the environmental conditions and postmortem processes involved in mummification, these cases illustrate the particular constellation of human behaviors and scenarios, as well as environmental conditions, which must coincide for this phenomenon to occur and highlight the necessity of the multidisciplinary approach to the medicolegal investigation of such deaths and the determination of the cause and manner of death.